Environmental and host factors associated with persistent lower respiratory tract symptoms or asthma following acute environmental exposure to sulphur dioxide (S02). - Baatjies, Roslynn (My University, 2007)
Introduction: On the weekend of 16 – 17 December 1995, the community of Macassar was exposed to elevated levels of sulphur dioxide vapours (SO2) caused by a fire on a nearby stockpile for approximately 21.5 hours. It has been estimated that community members were exposed to levels as high as 200 parts per million (ppm) of this gas as some 15 000 tons of the sulphur stockpile ignited. This resulted in a toxic plume of SO2 being blown over the Macassar area by the prevailing wind. The aim of this study was to assess the environmental and host factors associated with persistent lower respiratory symptoms among residents of this community six years after being acutely exposed to elevated exposures of SO2 vapours. Materials and methods: A case-control study was conducted. The cases and controls were selected from adult residents who reported to the Macassar disaster project clinic for a health assessment in order to lodge a medico-legal claim. Survey instruments included a questionnaire, clinical examination and clinical record review by an expert panel. A case was defined as an adult resident who presented to the clinic for an examination with persistent (at year 1 and 6 after the disaster) lower respiratory symptoms. Controls were chosen from clinic attendees without lower respiratory symptoms at year 1 and 6. Environmental exposure was calculated by using the Industrial Source Complex Short Term Model (ISCST 3) to predict time-averaged concentrations at specified receptor locations. Multiple logistic regression was used to investigate the association between lower persistent respiratory symptoms, host and environmental factors (estimated concentration and duration of exposure to SO2). Results: A total of 76 cases and 180 controls were selected. The cases and controls were comparable with respect to age, gender, height and smoking status. The results indicated that a medical history of pulmonary tuberculosis at least one year prior to the fire (OR: 3.5, CI: 1.5-8.4) was significantly associated with having persistent lower respiratory symptoms. Furthermore, subjects with persistent lower respiratory symptoms were nine times more likely to report symptoms of tight chest (OR: 9.9; CI: 5.2-19.1), and twice as likely to report shortness of breath (OR: 2.0; CI: 1.0-4.1) at the time of the fire. None of the exposure metrics (total hours of exposure, cumulative exposure, peak exposure) were significantly associated with persistent lower respiratory symptoms. However, peak SO2 exposure estimated at hour 15 was significantly associated with persistent lower respiratory symptoms (OR: 1.0; CI: 1.0-1.1). Discussion: The results of this study are consistent with previous studies reporting lower respiratory tract symptoms after chemical exposure irrespective of age or smoking status. Furthermore, as in other studies respiratory health status was a significant factor in determining susceptibility to SO2 exposure. Various reports in the literature suggest that exposure > 20 ppm is associated with chronic respiratory symptoms. This however was not demonstrated in this study, using estimates of exposure calculated using the ISCST model suggesting possible exposure misclassification. “Self-selection” bias was an important limitation in this study, since the entire study population was self-referred and as such the study population was not randomly selected. Another limitation is the possibility that there may be potential recall bias operating since the fire incident happened six years ago; however this was considered unlikely as there was nondifferential reporting between cases and control. Self reported symptoms on the questionnaires might have been over-reported due to fear, anxiety and stress or secondary gain related to compensation issues. The lack of association between exposure variables and persistent asthma may have also been due to lack of power (small sample size), although this was thought to be a minor contributory factor. Conclusion: Host-related factors such as a previous history of pulmonary TB and acute asthma-like symptoms at the time of the fire were important predictors of persistent lower respiratory symptoms reported by residents 6 years after acute exposure to SO2 vapours emanating from a sulphur fire.
Student Number : 0316118X - MPH research report - School of Public Health - Faculty of Health Sciences
Keywords: persistent lower respiratory symptoms; asthma; sulphur dioxide; exposure